(3MGTjI Ydi TQM GdeWhds - (3GdLQLGfj, GdTQja, Ydj Hf eMeO Hf Ydj, J (B816 (3g`s ((3Ydj CcHQs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPg MhGT Ydi GdTQM GdeTghQ dJdNjU GdeaJGM cfJ bO bjOJgG Ydjg eLedI Mjf eG bhdg Ydi HYV CMHc aGSCdhfj HYO CeI EPG aUdgG dge hGfbOgG aaYdJ Pdc eSJYjfG HGddg heJhcdG Ydjg (B...s
(3BNQgG (B:s
... (3hbO jchf GdeUdMI eTJQcI HjfgeG hcPdc Mcege HVeGf UGMH GdOGHI EPG ONdJ aj OGQ dG jNQL EdG HgOegG eJYddG HCfg deUMdI UGMH GdOGHI (B...(3hGdMeO ddgs
(3JHUQI GdYfhGf (B:s
(3GdeWhd ddJaJGRGfj TQM JdNjU GdeaJGM ddbRhjfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\7s
(3cTa GdXfhf (B1\473s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs